A review of reactive marketing on national parks and astro-tourism in Tanzania - Mkwizu, Kezia H. (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2024)
Astro-tourism has potential globally including Tanzania. For example, the skyline over Tanzania is filled with abundant astronomical objects like stars at night whereas on land, there is the famous Kimondo meteorite in Mbozi area. However, there is still challenge in tourism development particularly product diversification and marketing in the post-pandemic. Additionally, there are limited studies that connect visiting national parks and astro-tourism as co-activities that tourists can enjoy in protected areas. Therefore, the motive for this paper on astro-tourism is specifically to explore advertising of national parks and astro-tourism activities in Tanzania with a reactive marketing overview. An integrative literature review as a methodology approach is deployed in this study. Content analysis assisted to provide themes. The findings reveal that there are efforts made by the government and the private sector in advertising tourism including national parks. Also, the Royal Tour Film is one example of reactive marketing in the context of Tanzania as a way of advertising national parks. Findings also show that there is less advertising which connects national parks and astro-tourism within spaces of protected areas. The practical implication from this study is that the Destination Marketing Organizations (DMOs) and tourism stakeholders to engage more advertising that links national park activities and astro-tourism.